THIRD-CULTURE : IN TRANSLATION SEMIOTICS - Abdul Karim Panjaitan; Nurhikmah Panjaitan (Proceeding of International Conference on Language Pedagogy (ICOLP), 2024)
This study explores the concept of "Third Culture" within the context of semiotic translation. The study delves into the intricate process of semiotic translation, which involves the interpretation and communication of meaning across various cultural and linguistic boundaries. Examines how Third Culture navigates this complex terrain. This research sheds light on the role and opportunities of Third culture in semiotic translation, emphasizing their ability to act as cultural mediators and facilitators of cross-cultural exchange. The method of study is qualitative-descriptive and was conducted in Padang, West Sumatra, Indonesia. This study involved 8 students—5 students from the third culture and 3 students from the nonthird culture. The findings reveal the significance of cultural experiences in interpretation to achieve good translation for effective intercultural communication. The conclusion of this study shows that the role of third culture in translating semiotics is very important, and third culture has a great opportunity to produce good translations with clear meaning in translating semiotics.